Upaya Badan Pengawas Pemilihan Umum Dalam Meningkatkan Kinerja Panitia Pengawas Pemilu Di Kabupaten Seluma (Studi di Kecamatan Seluma) - Budiman Sakti; Haira Kuspita; Rahiman Dani; Henny Aprianty; Heru Purnawan (SENGKUNI Journal (Social Science and Humanities Studies), 2023)
Election oversight duties are carried out by the Election Organizing Body (Bawaslu). Bawaslu is also expected to be able to help prevent violations of clean, fair, and just elections. Bawaslu plays an important role as a focal point for the cases of candidate pairs, the winning team, and the organizers of the election itself. The purpose of the presence of an election monitoring body is to improve the quality of elections and reduce cases of election fraud. The purpose of this study is to discuss Bawaslu's strategy for improving the performance of the Seluma Regency Panwaslu in the 2019 Seluma Regency Simultaneous Pilkada and identify the obstacles of Bawaslu in improving Panwaslu's performance. The research was conducted at the Seluma Regency Bawaslu by interviewing seven people as research informants who were directly involved in the implementation of the 2019 simultaneous local elections at Bawaslu, Panwaslu, and regional leaders. Observations, interviews, and documentation are used as techniques and tools for data collection. The results of the study, based on respondents' responses to the indicators used in the research, it is known that the performance of Bawaslu in improving Panwaslu's performance in Seluma Regency has been good. This can be seen from the indicators analyzed: Productivity, Quality of Service, Responsibility, Accountability, and Responsibility in carrying out all tasks, including overseeing preparations for holding elections based on Article 101 of Law No. 7 of 2017. The suggestions of the Seluma Regency Bawaslu to improve the operationalization of the Seluma Regency Panwaslu provided Panwascam. with an understanding of the rules, legal basis and services to be provided, what to consider, what legal basis to use and what services to provide. Based on the mandate contained in the Pilkada Law No. 07 of 2017 as evidenced by various alleged violations, the Seluma Regency Panwascam will immediately inform the Seluma Regency Bawaslu according to the mandate.Â